(untitled) (CSIAM Transactions on Life Sciences, 2026)
Global warming and deteriorating environmental conditions have raised concerns about the persistence of green sea turtle populations, whose reproduction is governed by temperature-dependent sex determination. This study employs mathematical modeling to investigate these ecological challenges. Building on our previous models of green sea turtle population dynamics, we develop a sex-structured and stage-structured life history model that integrates temperature-dependent sex determination and ecological viability, offering a mechanistic framework for understanding green sea turtle population dynamics under climate and environmental stress. Our findings reveal that population dynamics are governed by an Allee-adjusted reproductive number, which accounts for both thermal and environmental influences. Additionally, we conduct a global stability analysis of the collapsed equilibrium using the singular perturbation approach, offering insights into long-term population viability. While additional parameter validation is necessary for definitive conclusions, our results illustrate how climate change and deteriorating environmental conditions shape the long-term viability of green sea turtle populations.